Решение задачи распределения нагрузки на основе динамической модели маршрутизатора - Кортунов, В. И.; Воробьев, А. В. (My University, 2011)
In the paper the problem of load balancing in the IP networks of access layer is analyzed. The method of local dynamic models carrying the balancing between routes with different metrics is proposed. The network with the proposed method is simulated.
Keywords: маршрутизация; уровень доступа; балансировка нагрузки; локальная модель